Self-Stigma of Mental Illness Among Latino People on the U.S.-México Border - Louden, Jennifer Eno; Esparza Del Villar, Oscar Armando; Avila, Alondra; Jung, Hyejin; Kosyluk, Kristin A.; Flores, Eduardo (2022)
People with serious mental illness often internalize society’s negative attitudes toward mental illness via self-stigma. Although stigma is a culturally defined construct, little is known about how stigma manifests among cultural subgroups in the United States. Negative consequences of self-stigma, such as reluctance to seek mental health treatment, may be particularly deleterious for members of certain ethnic groups, such as Latino people, who are already disproportionately at risk for not receiving mental health treatment. The goal of the present study was to examine how facets of culture explain variance in self-stigma among Latino people, and whether culture explained variance in self-stigma beyond sociocultural and mental health variables identified by prior research. We conducted a cross-sectional survey with a sample of 343 Mexican and Mexican American people who self-identified as having a mental health concern living in the U.S.-México border region. The survey assessed self-stigma, culture, mental health, and sociodemographics. We found that multiple facets of culture, namely collectivism, power distance, and long-term orientation, were significant predictors of variance in self-stigma even after controlling for mental health and sociodemographic factors. Although some factors identified by prior research can be used to understand self-stigma among Latino people, facets of culture appear important to consider. Cultural factors should be incorporated into antistigma interventions targeting the Latino community.